PENGARUH RISIKO PADA PROYEK PERLUASAN DAN RENOVASI HOTEL DI BALI TERHADAP BIAYA, MUTU, DAN WAKTU PELAKSANAAN PROYEK - Hardiana, IG.N Indra Cahya; Dharmayanti, G.A.P Candra; Budiwati, Ida Ayu Made (JURNAL SPEKTRAN; Vol 6 No 1 (2018): Vol. 6, No. 1, Januari 2018, 2018)
The project construction at the hotel wherein the existing hotel is still operating have higher risk than a new projects which starting from begining because the owner want the existing hotel still operate as usual during the construction project activity. This study aimed: to analyze the major risks that may occur in hotel renovation and extention project; and to analize their impact on the cost, time, and quality. Data collected by interviews and survey using questionnaires. Respondents were selected based on purposive sampling includes 71 respondents (contractors, consultants, owners and hotel operators) on this project. The data were analyzed by descriptive qualitative risk analysis. The number of the risks identification were 54 risks. 28 risks are categorized as major risk which sourced from criminality, permit, contract, pollution, natural conditions, price change, financial problems, project access, planning and design, project supervision and implementation, procurement, human resources, and social. That major risk such as pollution, limited access and land of projects, existing installation, the availability of existing material, contractor experience, partition blocks, and the time adjusment of project activities with hotel operational time. From that 28 major risks, 15 risks affect to the cost, 25 risks affect to the time, and only 3 risk affect to the quality. This study will be continued to formulate the actions to mitigate the major risks. Keywords: Cost, Hotel Renovation Project, Quality, Risk Management, Risk Mitigation, Time